Estimation of the enthalpy of formation for monosubstituted alkanes by 13C NMR chemical shift. (9th July 2020) - Wu, Yaxin; Tang, Kai
Abstract: The quantitative relationship between the 13 C nuclear magnetic resonance (NMR) chemical shift and the enthalpy of formation of monosubstituted alkanes was studied, and a new approach for calculating enthalpy of formation was proposed. The experimental values of the enthalpy of formation of 64 monosubstituted alkanes were correlated with the parameters SCS (the sum of chemical shift), P3 (path counts of length three bonds), n (the number of C atoms), h [X] (the contributions of the substituent X to the Δf H °(RX)), and the product of IPI (X) (the interaction potential index) and PEI (R) (the polarizability effect index). The regression results show a good correlation ( R = 0.9998, S = 4.5 kJ/mol). Its stability and prediction ability were confirmed by the results of the random sampling method and the leave‐one‐out method. In this paper, the 13 C NMR chemical shift and the enthalpy of formation of monosubstituted alkanes were associated quantitatively. The significance is not only to propose a new method to estimate the enthalpy of formation of monosubstituted alkanes, but also to establish a new method to understand the relationship between different properties based on a same molecular structure. Moreover, it provides a new approach for calculating a molecular difficult‐to‐test property parameter by means of another easy‐to‐test one. Abstract : The 13 C NMR chemical shift and enthalpy of formation of monosubstituted alkanes were associated quantitatively, and a new approach for calculating enthalpy of formation was proposed. The significance is not only to establish a new method to understand the relationship between different properties based on the same molecular structure, but also to propose a new approach for calculating a molecular difficult‐to‐test property parameter by means of another easy‐to‐test one.